Establishment and validation of a monoclonal cell-based reporter assay for screening of hypoxia-inducible factor activities - Liew, Sien Yei (2017)
Cell-based assay is a powerful tool in the fields of drug discovery. One of the main targets of current drug development is transcription factor. Hypoxia-inducible factors (HIFs) are transcription factors, which involve in cellular oxygen homeostasis and association with disease pathophysiology. Hence, manipulation of HIF activities in HIF-related diseases by HIF regulators is claimed to be an ideal and effective therapeutic therapy. Currently, a highly sensitive cell-based assay to measure HIF activity is still lacking in the market. Hence, the main objective in this study was to establish a highly sensitive HIF cell-based assay system that can quantitate HIF activity in high-throughput screening (HTS) format. This study described the development of a monoclonal, highly sensitive and stable reporter cell line for monitoring the activity of HIF by using luciferase reporter constructs. Four copies of hypoxia response element (HRE) of the erythropoeitin (EPO) gene, which is one of the targets of HIF, were used to drive the expression of the luciferase reporter. One of the monoclonal stable reporter cell lines, designated as Clone 3 (C3) gave a 500-fold increase in the luciferase signal in hypoxia, compared to a normoxia condition. This robust increase in hypoxia response is crucial to ensure consistency and reproducibility of HIF assay results while reducing the overall assay cost. The usefulness of C3 HIF assay system in measuring HIF activities was then confirmed by the proof of concept study using known HIFregulated drugs. After the establishment of the C3 HIF bioassay system, the bioassay system was validated on the HTS suitability factors rigorously in various experimental conditions. Data obtained in various HTS parameters such as robustness, linearity, specificity, intermediate precision and solvent compatibility of C3 HIF bioassay system were statistically controlled by coefficient of variation (CV) lower than 20% throughout the study, indicative of C3 HIF bioassay a reliable and controllable assay system for HTS format. The quality of C3 HIF bioassay was graded as excellent level by exhibiting Z-factor (Z') values that range from 0.524 to 0.954. Apart from the establishment and validation of this HIF assay system, the application of measuring HIF activities by C3 HIF assay system was evaluated using traditional medicinal plants in Malaysia in this study. Specific cytotoxic effects of traditional medicinal plant extracts under hypoxic conditions were observed in this study. Among nine tested traditional medicinal plants, methanolic crude C. papaya leaves extracts exhibited potent HIF inhibition. The dose-dependent HIF inhibitory effect was further confirmed by the use of C3 HIF bioassay system. Interestingly, C. papaya extracts were observed to be specific in targeting the hypoxic cancer cells by delineating significant lowered IC50 of cell proliferation compared to normoxic cancer cells. These findings highlight the importance of identifying specific traditional medicinal plant extracts which can be promising candidates for new approaches to eradicate hypoxic cancer cells in solid tumors. Thus, the establishment of this highly sensitive C3 HIF cell-based assay is concluded to be a promising approach to expedite research in the discovery of HIF regulatory drugs.